PENINGKATAN MINAT DAN HASIL BELAJAR ILMU PENGETAHUAN ALAM SISWA KELAS IV SD MENGUNAKAN MODEL PEMBELAJARAN NHT - Dwi Anjani, Gita; Mawardi, Mawardi (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2017)
Abstract : Learning science grade IV SDN Watu Agung 02 using NHT model canimprove student learning outcomes. This conclusion is based on the improvement of thesignificant learning outcomes of students who have completed in prasiklus, cycle I,cycle II is 41.17%, 58.82%, 88.23%. This research recommends that teachers can applythe model of learning Numbered Head Together (NHT) to improve students' learning outcomes in science subjects.ï€©SKBï€¨ in Cycle I to stay 2 students with the lowest scorewith very poor category ï€©SKBï€¨This study aims to increase students' interest and learning outcomes in IPA subjects using the Numbered Head Together (NHT) learningmodel. This type of research uses classroom action research, consisting of 2 cycles.Research subjects involving fourth grade students SDN Watu Agung 02 as many as 17students. The research instruments are questionnaire of interest, multiple choice test,and observation sheet. The technique of data analysis used is comparative descriptivetechnique by comparing the interest of learning and science learning outcomes betweencycles. Based on the results of research can be concluded the following: 1) learningscience grade IV SDN Watu Agung 02 using NHT model can foster interest in learningstudents in following science lesson. Evident from 4 students with low learning interestwith very poor category Keywords : Method Method of Learning Numbered Head Together (NHT), interest,